Die Städte im spanischen Amerika - Ein zeit-räumliches Entwicklungsmodell der letzten hundert Jahre - Gormsen, Erdmann (ERDKUNDE, 1981)
This paper outlines some of the changes in the spatial distribution of functions, social classes, and types of bulding in Spanish American cities. These changes have occurred in three stages: (1) the pre industrial town, preserving colonial patterns until the end of the 19th century, (2) an early phase of modernization (approx. from1900 to1950) with the establishment of some industries and with a European influence in architecture, (3) the recent urban sprawl resulting from massive immigration from rural areas, which was accompanied by a general metropolization. These clearly separated patterns are graphically demonstrated in fig.1, showing the inter relations between building structures, functions, land values, social status, and population density. The Mexican city of Puebla is taken as a case study.